System apProach To studying phenomenon of self-realization of individual - E U Shogoreva (Peoples' Friendship University of Russia (RUDN University), 2014)
This article analyzes the phenomenon of self-realization. The author of the article is trying to consider the self-realization from the position of the system paradigm. That position allows looking into the problem of self-realization and the factors of self-realization in a new way.